Caring for Relatives with Dementia in Times of COVID-19: Impact on Caregivers and Care-recipients. Issue 1 (1st January 2022) - Losada, Andrés; Vara-García, Carlos; Romero-Moreno, Rosa; Barrera-Caballero, Samara; Pedroso-Chaparro, María del Sequeros; Jiménez-Gonzalo, Lucía; Fernandes-Pires, José; Cabrera, Isabel; Gallego-Alberto, Laura; Huertas-Domingo, Cristina; Mérida-Herrera, Laura; Olazarán-Rodríguez, Javier; et al.
ABSTRACT: Objectives: To analyze caregivers' perceived impact of the pandemic in their mental health and the well-being of the care-recipients. Methods: Caregivers (N = 88) were asked if they had COVID-19 and about their perceptions of change of care-recipients' health conditions as well as whether their own mental health, conflicts with care-recipients and other relatives, thoughts of giving up caregiving, and feelings of coping well with the situation. Results: A large percentage of caregivers perceived a worsening of care-recipients' symptoms and of their own negative emotions, an increase in the number of conflicts and thoughts of needing to give up caregiving. Having had COVID-19 and reporting higher levels of distress as well as giving up caregiving were related to perceived worsening in care-recipients well-being. Perceived increases were mainly reported by younger caregivers, those who perceived to have not coped well, and those reporting an increase in conflicts. Some caregivers perceived an increase in positive emotions. Conclusions: The pandemic has a negative impact on caregivers' perceptions about the course of their own emotions and care-recipients' well-being. Clinical implications: Interventions are needed to train caregivers in strategies to cope with the sources of stress caused by the pandemic and to promote social support.